Antibacterial surface design – Contact kill. Issue 3 (August 2016) - Kaur, Rajbir; Liu, Song
Abstract: Designing antibacterial surfaces has become extremely important to minimize Healthcare Associated Infections which are a major cause of mortality worldwide. A previous biocide-releasing approach is based on leaching of encapsulated biocides such as silver and triclosan which exerts negative impacts on the environment and potentially contributes to the development of bacterial resistance. This drawback of leachable compounds led to the shift of interest towards a more sustainable and environmentally friendly approach: contact-killing surfaces. Biocides that can be bound onto surfaces to give the substrates contact-active antibacterial activity include quaternary ammonium compounds (QACs), quaternary phosphoniums (QPs), carbon nanotubes, antibacterial peptides, and N -chloramines. Among the above, QACs and N -chloramines are the most researched contact-active biocides. We review the engineering of contact-active surfaces using QACs or N -chloramines, the modes of actions as well as the test methods. The charge-density threshold of cationic surfaces for desired antibacterial efficacy and attempts to combine various biocides for the generation of new contact-active surfaces are discussed in detail. Surface positive charge density is identified as a key parameter to define antibacterial efficacy. We expect that this research field will continue to attract more research interest in view of the potential impact of self-disinfective surfaces on healthcare-associated infections, food safety and corrosion/fouling resistance required on industrial surfaces such as oil pipes and ship hulls.